How Websites have impacted the sports journalism industry - Meyer, Adam (Kansas State University, 2024)
The concept of a sports journalist starting an independent website, gaining an audience and establishing a brand with the website, and attracting a larger media company to purchase the business, has become a common practice. There have been instances where a website has sold at a low price, and there have been instances where the publisher of the website made a lot of money from the sale. This report will explain how this idea of independent sports websites came about, and why they are sold to a media business to further the gains of the website. This report will discuss the overall transition from the focus of the printed newspaper to online. This topic is important because it offers clear guidance and understanding of how the sports journalism business, and the journalism industry, has transitioned from the printed newspaper to the web. This is important because journalism is how news is disseminated to the general public and how viewers see advertisements. This report will examine examples of independent sports journalism websites founded by individuals, then discuss how they came to be purchased by businesses as well as the purchase benefits to both parties.
Keywords: Print transition to internet